Rural Education in Latin America and the Caribbean: Past and Present - Mansilla Sepúlveda, Juan Guillermo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2023)
This issue of the Journal Historia de la Educación Latinoamericana focuses on the debate on the historical perspective of Rural Education (Educação do Campo) in some territories of Latin America and the Caribbean. It presents a dossier with twelve articles largely dedicated to schools, teachers and students who have left relevant traces in the rural schools of Latin America (Abya-Yala). Rural education is, in essence, the social environment in which the deployment of expansive and inclusive learning acquires true meaning, since schools located in the countryside respond permanently to the requirements of their social and cultural environment. Nevertheless, and based on the available empirical evidence, we dare to say that the socio-historical constitution of the social distribution of knowledge is markedly unequal in rural school worlds. The school system, in general, has contributed to reproduce this inequality.